PENGELOLAAN PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. PLN (PERSERO) UNIT INDUK WILAYAH SULSELRABAR KOTA MAKASSAR - Fina Fina; Andi Rosdianti Razak; Ansyari Mone (Program Magister Ilmu Administrasi Publik, Universitas Muhammadiyah Makassar, 2022)
The purpose of this study was to determine the Management of Corporate Social Responsibility (CSR) Programs at PT. PLN (Persero) Main Unit for South Sulawesi Region, Makassar City. This study used a qualitative research and descriptive research type. Research informants amounted to 5 people. Data collection techniques used observation, interviews, and documentation. The results showed that the Management of the Corporate Social Responsibility (CSR) Program of PT. PLN (Persero) Parent Unit for Sulselrabar Makassar City which started from: 1) Planning was categorized as having succeeded in managing CSR programs as evidenced by real programs that really help the community. 2) The organization of the PLN response was fast and involved directly. 3) Providing motivation was important in order to strengthen relationships and become a driver so that the target was achieved. 4) Supervision must be greatly improved to ensure that the ongoing program was in accordance with the plan and involved the community. 5) The community assessment feels cared because it had been given assistance through the CSR program and was expected to continue.